Leucomethylene blue probe detects a broad spectrum of reactive oxygen and nitrogen species. Issue 51 (29th September 2021) - Cremer, Christopher; Merkes, Jean Michél; Bub, Christina L.; Rommel, Dirk; Patureau, Frederic W.; Banala, Srinivas
Abstract : A broad spectrum ROS/RNS sensing butylated phenol tethered leucomethylene blue is presented. This probe detects a variety of ROS/RNS, with up to 100-fold gain in fluorescence in the red range, is suitable for microscopic and macroscopic in vivo fluorescence imaging. Abstract : Reactive oxygen and nitrogen species (ROS, RNS) are ubiquitous in biology with a variety of physiological and pathological functions. Here we describe a broad spectrum ROS/RNS detecting fluorogenic probe with red fluorescence emission and up to 100-fold gain. Hence these modified probes are useful for in vivo non-invasive quantification of ROS/RNS.